A phenomenological analysis of the spiritual development of psychotherapists who work with sexual violence survivors - Waters, J. Mitchell; Conley, Abigail Holland (Frontiers in Psychology, 2025)
Religion and spirituality play a large role in the lives of many counselors who work with survivors of sexual violence. Indeed, engagement in this clinical work may play a role in the counselor's spiritual development. In this phenomenological study, we examined the faith development experiences of religiously and spiritually diverse counselors and psychotherapists who work with survivors of sexual trauma. Through semi-structured interviews with eleven participants, the researchers identified two main themes: (1) transformative faith experiences and (2) religion as a barrier. The findings of this study highlight the intricate relationship between spirituality and faith development that counselors navigate when engaged in the challenging work of supporting survivors of sexual violence over extended periods.